Measure color stability of red cabbage using different solvents - Mohd Azri, Ahmad (2010)
Color is one of most important properties of foods and beverages and is a basis for their identification and acceptability.The use of natural colorants has generated considerable interest nowadays as an alternative to synthetic colorants.Consumer concern over the safety of synthetic food colorants has increased the demand for natural food colorants.Our objective of this research is to determine the color stability of red cabbage based on storage days by using different solvents.Color was determined using CIE system L*, a*, b*.The color stability of red cabbage is based on L*, a*, b* values.Red cabbage was extracted with different volume concentration of solvents used.The solvents used for this extraction are methanol and ethanol.Based on the results,we can conclude that the color of red cabbage is most stable when extracted with 40% methanol.